Experimental Investigation of Multi-stage Robot-Assisted Single Point Incremental Sheet Forming of Al 6061 Sheet - Singh R.P.; Kumar S.; Singh P.K.; Meraz M. (My University, 2025)
Incremental sheet forming is a die-less forming method to deform the sheet in a stepwise manner to get the final product. In the current work, the Al 6061 sheet has been deformed using single point incremental sheet forming methodology on 6-axis industrial robot to produce a single wall angle and double wall angle conical shape. The wall angle of 68.2° has been obtained using a multi-stage forming strategy. Two types of tools, namely roller ball tool and fixed ball tool have been deployed to accomplish the process. The deformed sheet has been investigated for sheet thinning and surface finish. The quality of the product in terms of forming depth, greater wall angle, and surface finish is better for multi-stage incremental sheet forming. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.